Pengaruh Literasi Keuangan Syariah Terhadap Minat Menggunakan Fintech Peer to peer (P2P) Lending Syariah: Studi Kasus Masyarakat di Jabodetabek - Kahar Muzakkar; Nurizal Ismail; Solahudin Al-Ayyubi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of variables such as knowledge, ability, attitude, and trust on the interest in using Shariah Peer to peer (P2P) Lending Fintech: A Case Study of Communities in Jabodetabek. The data source of this research is primary data derived from a sample of residents in Jabodetabek. Data collection was conducted by distributing questionnaires to 100 respondents. The analysis method used is Partial Least Squares Structural Equation Modeling (SEM-PLS) technique using SmartPLS.3 software. The results of this study indicate that all four variables significantly influence interest and engagement of the community in using Shariah fintech services. It emphasizes the complexity of factors influencing the adoption of Shariah financial technology.